Senior High School Students’ Perceptions of Online Learning During the Pandemic Era - Islamiaty, Dian; Putro, Nur Hidayanto Pancoro Setyo; Alrahhal, Maher (International Journal of Contemporary Studies in Education, 2023)
This descriptive qualitative study is based on the implementation of online learning by the government during the pandemic era. Online learning system requires students and teachers to take advantage of existing technology to keep learning even though they do not meet each other. During the pandemic, almost all students in Indonesia experienced online learning by utilizing applications such as zoom and google meet. The purpose of this study is to discover the perceptions of XI grade students at SMA N 1 Patimuan for the academic year of 2021/2022 during the implementation of online learning in the pandemic era. All data obtained through questionnaires distributed using google form. The subjects of this study were the 112 students of XI grade at the SMA N 1 Patimuan. The study found that students felt dissatisfied and experienced some challenges during the implementation of online learning. From their point of view, the disadvantages of online classes outnumber the benefits. The lack of understanding about online learning applications, weak internet connectivity, poor interaction with others, and hard to understand the materials are the most challenges found